TRANSLANGUAGING PRACTICES IN EFL CLASSROOMS: EVIDENCE FROM INDONESIA - Gede Eka Putrawan (CaLLs: Journal of Culture, Arts, Literature, and Linguistics)
The aim of this paper is to elucidate a comprehensive perspective on translanguaging practices in EFL classrooms in Indonesia by reviewing empirical literature published in scientific journals and/or proceedings focusing on four primary areas, which include: (1) research methodology, (2) advantages and disadvantages of translanguaging, (3) languages used when translanguaging, and (4) perceptions and attitudes toward translanguaging. The findings indicate all of the studies under review were conducted through a qualitative approach with the instruments of observations, interviews, and questionnaire. Teachers and students have the benefit of translanguaging practices in EFL classrooms, yet it should be taken into account that L1 should be adopted judiciously. They translanguage using English, Indonesian, and local languages and even foreign languages other than English. They have voiced their agreement to the implementation of translanguaging as pedagogy since it positively impacts EFL teaching and learning. However, few teachers have contrasting views about this voice. Suggestions for future research on translanguaging are also discussed.